Primary cutaneous B-cell lymphoma and chronic leg ulcers in a patient with type 2 diabetes - Alessandro Mantovani; Fabrizia Perrone; Vincenzo Stoico; Isabella Pichiri; Laura Salvotelli; Ilaria Teobaldi; Massimiliano Bruti; Michela Conti; Luca Cima; Albino Eccher; Enzo Bonora (Endocrinology, Diabetes & Metabolism Case Reports, 2017)
The incidences of type 2 diabetes mellitus and many cancers are rapidly increasing worldwide. Diabetes is a strong risk factor for some cancers (including lymphomas) and is also associated with adverse cancer outcomes. After gastrointestinal tract, the skin is the second most frequent extranodal site involved by non-Hodgkin lymphomas and the cutaneous B-cell lymphomas (CBCLs) range from 25% to 30% of all primary cutaneous lymphomas. The primary cutaneous diffuse large B-cell lymphoma (PCDLBCL) is an aggressive lymphoma with a poor prognosis, representing roughly 20% of all primary CBCLs. Classically, the cutaneous manifestation of this lymphoma is a red or violaceous tumors arising on a leg. To date, despite the large body of evidence suggesting that diabetes is strongly associated with an increased risk of some cancers, very little information is available regarding a possible association between type 2 diabetes and primary cutaneous diffuse large B-cell lymphoma. In this report, we will present the case of a white adult patient with type 2 diabetes with chronic leg ulcers complicated by a primary cutaneous diffuse large B-cell lymphoma.